Cognitive Deficits Are Attenuated in Neuroglobin Overexpressing Mice Exposed to a Model of Obstructive Sleep Apnea - Nair, Deepti; Ramesh, Vijay; Gozal, David (Frontiers in Neurology, 2018)
Background: Obstructive sleep apnea (OSA) is a highly prevalent disease manifesting as intermittent hypoxia during sleep (IH) and is increasingly recognized as being independently associated with neurobehavioral deficits. These deficits may be due to increased apoptosis in the hippocampus and cerebral cortex, as well as increased oxidative stress and inflammation. It has been reported that neuroglobin (Ngb) is upregulated in response to hypoxia-ischemia insults and exhibits a protective role in ischemia-reperfusion brain injury. We hypothesized that transgenic overexpression of Ngb would attenuate spatial learning deficits in a murine model of OSA. Methods:Wild-type mice and Ngb overexpressing male mice (Ngb-TG) were randomly assigned to either IH or room air (RA) exposures. The effects of IH during the light period on performance in a water maze spatial task were assessed, as well as anxiety and depressive-like behaviors using elevated plus maze (EPM) and forced swim tests. Cortical tissues from all the mice were extracted for biochemical studies for lipid peroxidation. Results:Ngb TG mice exhibited increased Ngb immunoreactivity in brain tissues and IH did not elicit significant changes in Ngb expression in either Ngb-TG mice or WT mice. On a standard place training task in the water maze, Ngb-TG mice displayed preserved spatial learning, and were protected from the reduced spatial learning performances observed in WT mice exposed to IH. Furthermore, anxiety and depression levels were enhanced in WT mice exposed to IH as compared to RA controls, while alterations emerged in Ngb-TG mice exposed to IH. Furthermore, WT mice, but not Ngb-TG mice had significantly elevated levels of malondialdehyde in cortical lysates following IH exposures. Conclusions:In a murine model of OSA, oxidative stress responses and neurocognitive and behavioral impairments induced by IH during sleep are attenuated by the neuroprotective effects of Ngb.